Assessing respiratory exposure to harmful evaporations in a manufacturing company - Jaddi Madarsara, Tayyebeh; Ahmadian Kudakan, Navid; Yari, Saeed; Saeidabadi, Hamzeh (Asian Pacific Journal of Environment and Cancer, 2019)
Introduction: Using Hypochlorite Sodium in producing bleaches in order to disinfect and shine surfaces has been an ordinary method since 200 years ago. 10-15% solutions with PH=13 have been used for industrial purposes and 5% solutions with PH=11 have been used for domestic use. AIHA (American Industrial Hygienists Association) has announced the maximum standard exposure to this substance equal to 2mg/m3 in a period of 15 minutes. It should be noted that, based on material safety data sheet and NFPA rating explanation guide, the mentioned substance is mildly unstable (code 1), carries oxidation hazard (ox), and serious respiratory hazard (code 3). Methods: This survey has been conducted with statistical society of 39, average age of 29.82±3.66 and work experience of 2.46±6.02 who were exposed to Hypochlorite Sodium in 2019. The reference of analyzing the data include medical check-up inventory, spirometry FEV1, FVC, and FEV1/FVC relativity, using SPSS ver16, and T-test. Results: The statistical society (39 participants) had a normal distribution, with a very pleasant correlation amounts in (FEV1/FVC, FVC, FEV1) considering sig=0.13, andless possibility than (P≤0.05). therefore, the amounts before and after FEV1, and FEV1/FVC, had a meaningful difference statistically, however, taking the amount of sig=0.68 into account which was P≤0.05, no meaningful difference was observed for FVC amounts before and after respiratory exposure to Hypochlorite Sodium. Conclusion: Considering the reduction in amount of FEV1, and FEV1/FVC among the workers of the manufacturing site who were exposed to Hypochlorite Sodium, they are likely to have pulmonary obstruction, and therefore they are required to be changed in position and location of their jobs, and also appropriate ventilation system must be installed in the location of Hypochlorite Sodium evaporations. Keeping in mind the instability and corrosiveness of Hypochlorite Sodium, all employees had better use respiratory masks (preferably FFP3 in case of dusty materials), proper face shields, anti-acid gloves, anti-acid overalls, and chemical resistant boots. Keywords: Respiratory exposure assessment, Occupational Asthma, Hypochlorite Sodium, Bleach, FEV1, FVC, FEV1/FVC, CANCER.